Medical expulsion therapy in the management of ureteric calculi: a comparative real-life experience - Degaonkar, Anil S.; Jamdade, Pundlik T.; Bhamare, Nikhil S.; Shirure, Prashant A.; M. S., Manjuprasad; Swami, Onkar C. (International Surgery Journal, 2017)
Background: One of the conservative management of ureteric caculi is by medical expulsive therapy by targeting common causes of obstruction such as edema, ureteral spasm and infection which will favour expulsion of calculi. The objective of this study was to assess comparative efficacy and safety of medical expulsive therapy of ureteric calculi. Methods: This was a randomized, prospective, open label, comparative study. Subjects satisfying inclusion and exclusion criteria were randomized into 4 groups tamsulosin, nifedipine, progesterone and control. Medical expulsion of calculi of 6mm to 15 mm size was carried out in 120 patients. Patients were followed up on OPD basis every third day. Calculi expulsion until day 28 as confirmed by abdominal ultrasonography was taken as the end point. Results: Expulsion rate in tamsulosin group was 90%, whereas nifedipine, progesterone group were 83.33% and 70% respectively which was significant compared to control group which was 36.6% (p < 0.005). Expulsion time was also reported to be significantly less in these groups as compared to control group. Therapy related adverse effects were minor and were seen in only 6 patients. Conclusions: Medical expulsive therapy of ureteric calculi of size 6 to 15mm with Tamsulosin, nifedipine and progesterone were safe and efficacious and could be implemented for initial management in selected patients.